Predictors of early attrition and successful weight loss in patients attending an obesity management program - Jiandani, Dishay (BMC Obes, 2016)
BACKGROUND: Our objective was to identify factors that are independently associated with early attrition and successful weight loss (WL) in an obesity-management program. METHODS: Participants were 9,498 patients enrolled in treatment at the Wharton Weight Management Clinic for at least 6 months. Predictors of early attrition (<6 months) and successful WL (≥5 %) were analyzed using relative risk (RR) in men and women separately. Pearson’s correlation was used to determine the relationship between WL and treatment time Weight loss and attrition analysis was restricted to patients who had more than two visits (n = 5415). RESULTS: Older individuals had lower early attrition (RR Range:0.74–0.92, P < 0.05) and greater WL success (RR Range:1.40–1.65, P < 0.05) than younger individuals. Males with hypertension and females with depression had greater early attrition (RR Range:1.09–1.20, P < 0.05) and lower WL success (RR Range:0.48–0.57, P < 0.05) than those without these health conditions. Males with lower education had greater early attrition (RR = 1.11[1.03–1.19]) than males with higher education, but did not differ in WL. Females who smoked had greater early attrition (RR = 1.06[1.01–1.11]) than females who did not smoke, but did not differ in WL. Ethnicity was not related to early attrition, however, females of Black and Other ethnicities had lower WL success compared to White females (RR Range:0.58–0.74, P < 0.05). After adjusting for treatment time, all above associations were no longer significant and treatment time remained as the only independent predictor of WL success (P < 0.0001). CONCLUSION: As WL is positively and independently related with treatment time, individuals at risk for early attrition may need alternative treatment options, in order to improve patient retention and improve WL success.